Ecotoxicological assessment of Zn, Cu and Ni based NPs contamination in Arenosols - Sergey Kolesnikov; Аlena Timoshenko; Tatiana Minnikova; Tatiana Minkina; Vishnu D Rajput; Kamil Kazeev; Morteza Feizi; Elena Fedorenko; Saglara Mandzhieva; Svetlana Sushkova (Universitas Sebelas Maret, 2021)
Nanoparticles are increasingly used in many industrial fields because of their special properties. In this context, several questions arise related to possible negative consequences associated with nanoparticle (NPs) entrance into the ecosystem. The adsorption of NPs by soil can adversely influence its biological properties. In the present article, the influence of Cu, Zn, and Ni NPs on the biological characteristics of Arenosol is considered. Research aimed to study the effect of Cu, Zn, Ni NPs on the biological characteristics of sandy loam chernozem. Copper, Zn, and Ni NPs were added to the soil in concentrations of 100, 1,000, and 10,000 mg kg-1. The effect of NPs on the biological properties of Arenosol was evaluated after 10-day incubation. The biological indices of the ecological condition of the soil, including the germination of radish, the length of the roots, the bacteria population, Azotobacter sp. count, the catalase activity, and dehydrogenases were studied. As a result of this study, it was revealed that the degree of indices changes depending on the concentration of Cu, Zn, and Ni NPs in the Arenosols. Microbiological characteristics (bacteria population, and Azotobacter sp. count) and phytotoxic feature (length of roots and radish germination) properties were most sensitive to contamination compared to the enzyme activity of Arenosol. Based on the soil integral index of a biological state, the strongest inhibitory effect on biological parameters of Arenosols relative to the control was exerted by Cu NPs (lower than control by 48-72%), while the greatest stability in Arenosol was found for Ni NPs (lower than control by 30-55%). The studied biological parameters allow characterizing the severity of nanoparticle exposure on Arenosols. Early diagnostics of the severity of soil contamination by NPs can be successfully used to quickly assess their impact on the soil condition and prevent possible adverse consequences.